Association of volunteering with mental well-being: a lifecourse analysis of a national population-based longitudinal study in the UK. Issue 8 (8th August 2016) - Tabassum, Faiza; Mohan, John; Smith, Peter
Abstract : Objectives: The association of volunteering with well-being has been found in previous research, but mostly among older people. The aim of this study was to examine the association of volunteering with mental well-being among the British population across the life course. Design: British Household Panel Survey, a population-based longitudinal study. Setting: UK. Participants: 66 343 observations (person-years). Main outcome measures: Mental well-being was measured by using the General Health Questionnaire (GHQ-12 or GHQ); high values denote high mental disorder. Four groups of volunteering participation were created: frequent (once a week), infrequent (once a month/several times a year), rare (once or less a year) and never. Multilevel linear models were used to analyse variations in mental well-being over the life course by levels of volunteering. Results: When not considering age, those who engaged in volunteering regularly appeared to experience higher levels of mental well-being than those who never volunteered. To explore the association of volunteering with the GHQ across the life course, interaction terms were fitted between age and volunteering. The interactions were significant, demonstrating that these associations vary by age. The association between volunteering and well-being did not emerge during early adulthood to mid-adulthood, instead becoming apparent above the age of 40 years and continuing up to old age. Moreover, in early adulthood, the absence of engagement in voluntary activity was not related to mental well-being, but GHQ scores for this group increased sharply with age, levelling off after the age of 40 and then increasing again above the age of 70 years. The study also indicates variation in GHQ scores (65%) within individuals across time, suggesting evidence of lifecourse effects. Conclusions: We conclude that volunteering may be more meaningful for mental well-being at some points of time in the life course.